Sosialisasi Peluang Home Business dalam Ekonomi Digital - Muhammad Wali; Khairul Amri; Nasir; Syamsul Rizal; Abdus Salam (Yayasan Kawanad, 2022)
This socialization activity aims to provide insight into opportunities to develop knowledge of trends and insights that are equal for small industries, as well as educate participants to obtain information to be able to join relevant associations/communities in every expert activity on social media. The implementation method follows a gradual process consisting of stages of information exchange, question and answer, discussion, and demonstration. The enthusiasm of the participants who followed with a percentage of 94%, and the results that have been achieved in the activities carried out are; 1) Participants are familiar with the knowledge and opportunities of home industry, 2) Participants are able to master the use of the Canva application to create product catalogs and implement it on various online sales media platforms, 3) Participants are able to take advantage of relevant associations/communities in every expert activity in the media social media to obtain relevant information, and 4) Participants are also able to master the knowledge gained as additional skills and create effective product promotion opportunities for home industries.